Training and Assistance for Housewives' Group to Create a CEHATI Family (Smart, Healthy, and Active) in Efforts to Maintain Children's Health - Anwar, Lufthiani; Nasution, Siti Zahara; Siregar, Cholina Trisa; Sitepu, Nunung Febriany (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The school age is a critical period, because at this time infectious diseases often occur in children. The incidence of infectious diseases in children is increasing which will have an impact on the growth and physical development of children. The role of mother is very important such as in the implementation of health services for children and families in order to make efforts to prevent infectious diseases in children. The purpose of training and mentoring activities by forming a CEHATI (Smart, Healthy and Active) family can increase the knowledge and skills of mothers in efforts to maintain children's health at home. The method of implementing community service activities is carried out by providing education, training and assistance to 50 housewives groups. Education is carried out by providing health education about disease problems in children, PHBS and Handling the Risk of Injury to children, followed by simulation and training on handling injuries at home and providing assistance. The results of the implementation of this community service activity showed that the mother's knowledge of infectious diseases and PHBS was in good category (100%), after training and mentoring activities were carried out. The results of the paired t-test before and after being given training and mentoring obtained a p value of 0.000. As a result of this activity, it is hoped that the group of housewives can increase their knowledge and be independent in efforts to maintain children's health so that they are formed into a CEHATI (Smart, Healthy and Active) family.